O processo de didatização dos saberes linguísticos em livros didáticos de língua portuguesa dos anos 1970 e 1980 no Brasil - Silva, Jaíne de Fátima Machado da (2024)
This work aims to understand how linguistic authors put into operation the process of didatization of linguistic knowledge in Portuguese textbooks of the 1970s and 1980s. The theoretical perspective adopted is given by the articulation of the French Discourse Analysis with the History of Linguistic Ideas. The research archive consists of three Portuguese language textbooks: Português oral e escrito, from 1978, by the author Dino Preti; Novo Português Através de Textos, from 1982, by the author Magda Soares; and Comunicação em Língua Portuguesa of 1983, by the authors Carlos Faraco and Francisco Marto de Moura. The corpus consists of Discursive Sequences cut from the initial section of each of the books, which receive different nominations in each of them. In the first book, it is entitled “Ao professor “; in the second, “Apresentação”; and in the third “A orientação desta obra”. These Discursive Sequences constitute Discursive Clippings, organized from questions that lead us to interpretative gestures related to our goal. Our interpretative gestures, throughout the work, showed that the way linguists authors put into operation the process of didatization of linguistic knowledge in Portuguese textbooks of the 1970s and 1980s - more precisely of the years 1978, 1982 and 1983 - is a process put into operation from various factors, such as the formation of these authors and their conceptions about the textbook, political implementations, and intellectual productions of the time, with regard to linguistic Science.